Evaluating the adoption of agile project management practices in Chinese technology companies: Risk management implications - Lei Cheng (Diversitas Journal)
This research explores on the results of a mixed-methods study conducted to explore the adoption of Agile Project Management (APM) practices and associated risk management implications in China manufacturing companies. Without repeating the detailed list of research questions, it is helpful to recall that our study sought to explore what leads tech firms in China towards adopting APM practices, as well as risk mitigation strategies; and how such risk management could be integrated successfully into a broader strategic framework in the technology sector within the Chinese context. The research used a survey of 223 employees in Jiangxi Province, China in 10 technology companies coupled with qualitative interviews and focus groups. Our quantitative analysis consisted of descriptive statistics, ANOVA and regression analysis while for the qualitative data we used thematic analysis. The survey showed strong adoption of APM practices, as well as the keys to success: Culture, Bi-modal approach and Benchmarking rated "Often Adopted." Nevertheless, wide differences in adoption and risk management practices were identified among different organizational roles: senior management and Scrum Masters displayed higher rates than some other roles. The strongest factor predicting risk mitigation practices in relation to individual characteristics was environmental factors, that were followed by organizational and cultural factors. The study provided insight into some of the challenges faced in tailoring APM to suit Chinese organizational culture, especially in aligning agile principles with top-down and hierarchical governance frameworks. It reinforced for me the need to have a real physical workspace designed in an agile way and supported by technology. Based on these findings, a strategic framework was developed for integrating APM and risk management, emphasizing organizational alignment, cultural adaptation, continuous learning, and environmental responsiveness. The study contributes to the understanding of APM adoption in culturally distinct business environments and offers practical insights for technology companies in China seeking to enhance their agile practices and risk management strategies